Journal of Aeronautics and Space Technologies (JAST) - Tuncay Gürbüz (Havacılık ve Uzay Teknolojileri Dergisi, 2019)
As the competition gets more and more fierce in today’s markets, companies have to have an effectively chosen strategy in order to acquire better place in the market in which they are active. The SPACE Matrix method was once a useful method to analyze the competitive position of an organization using internal and external dimensions. However within its basic idea it is pointed out that it has some drawbacks. Therefore it has become obsolete nowadays because of those drawbacks and in order to resuscitate it, in this study, some of those drawbacks are pointed out and a way of coping with it using well known Analytic Hierarchy Process (AHP) and Analytic Network Process (ANP) methods is presented. Thus a hybrid strategy determination tool has been presented.